Evaluasi efek suplementasi vitamin D dalam pencegahan preeklampsia: Literature review - Rista Dwi Hermilasari (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: A pregnancy complication accompanied by hypertension and proteinuria as a cause of maternal morbidity and mortality is preeclampsia. Vitamin D deficiency in pregnant women can cause adverse pregnancy outcomes. Vitamin D is an important micronutrient during pregnancy that potentially prevent preeclampsia.Objectives: The purpose of this review is to evaluate the effect of vitamin D supplementation in preventing preeclampsia.Methods: This narrative literature review is using article tracer from Google Scholar and PubMed database with publication in last ten years. This article search is using keywords “vitamin D”,  “hypovitaminosis D”, “pre-eclampsia”, “preeclampsia in pregnancy”, and “vitamin D supplementation”. The data collection technique used a narrative review of six literature regarding the effectiveness of vitamin D in preventing preeclampsia. Research data analysis includes creating research questions, searching articles according to keywords on inclusion criteria, reviewing abstracts and literature content, and reviewing document results.Results: Vitamin D deficiency contributes to the development of preeclampsia. Several studies have found that the incidence of preeclampsia increases in pregnant women with vitamin D deficiency. Serum vitamin D levels in pregnant women with preeclampsia are lower than in pregnant women without preeclampsia. Vitamin D supplementation is effective to rise vitamin D blood concentrations and can also lowering the risk of preeclampsia.Conclusion: Vitamin D supplement proves beneficial throughout pregnancy as an adjuvant therapy for reducing the incidence of preeclampsia. Keywords :Maternal preeclampsia, Pregnancy, Vitamin D, Vitamin D deficiency